(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Whether experienced on social media or in person, the findings of modern psychology consider the effects of body shaming—in terms of skinny shaming, fat shaming, dwarf shaming, or giant shaming—detrimental to mental health. This study explores how the slurs of body shaming on social media (Facebook, Instagram, Twitter, etc.) and in actual life affect the mental health of young adults and shake their confidence in different walks of life. Both men and women report experiencing it to different degrees and levels. The study also enlists the perfectionist trends that are advertised as well as promoted by different consumerist brands and firms in the make-up, body-shaping, and body-health care industries. With qualitative and interpretive analysis, the study conducts a case study of Rawalpindi with a sample of 12 (female [06] and male [06]) residents, whose semi-structured interviews are in-depth analyzed with Higgins’ (1987) theory of “Self-Discrepancy”. The findings of the study drawn from target interviews attest to the fact that—with a slight variation—both men and women have been victims of body shaming both on social media and in actual life. Next, the findings of the study categorically mark social media as a chief source of normalizing the in-fashion beauty standards against casual human shapes, which, at large, shape public opinion and shrink room for the casual physiques in society. Such trends, both consciously and unconsciously, bound the casual victims to meet the standards of in-fashion beauty standards (which resultantly benefits the advertising industries) and to avoid low criticism, body slurs, criticism, self-esteem, depression, and lack of confidence. The study is highly significant for the health of a balanced society and corresponds to UN SDG No. 03 (Good Health and Well-being).